(untitled) (International Journal of Food and Nutritional Sciences, 2020)
Hyderabadi Mix can refer to a few different things depending on the context, but it’s commonly associated with a blend of spices, or a mix of various ingredients, often used in Indian cuisine. Protein energy malnutrition (PEM) remains a challenging health issue among under five children in almost every developing nations of the world let alone India. Hyderabad mix can be used to improve the weight gain and nutritional status among under five children. The aim of the study was to assess the effectiveness of Hyderabad mix on nutritional status among under five children belonging to tribal community. A study was done to find the effectiveness of the Mult interventional approach on knowledge regarding demonstration & distribution of Hyderabadi Mix to prevent the nutritional deficiencies among mothers of under-five children in rural areas, Kanpur. The research approach for the present study is a Quasi experimental Research approach, The research design selected for the study one group pre-test and post-test design. The conducted in some selected rural areas, Kanpur District, Uttar Pradesh. The sample was under -five mothers in rural areas, Kanpur District, Uttar Pradesh. Convenient sample technique going to use. Data was collected from 600 mothers. In result it shows that there was no previous knowledge regarding the Hyderabadi Mix & after the Mult interventional approach it shows that there was 60% mother who are having adequate knowledge & 40% having moderate knowledge and it shows that there are all the demographic variables are highly associated with pre-test knowledge except education status & family income at the level of 0.05.